Identification and characterization of biomarkers associated with endoplasmic reticulum protein processing in cerebral ischemia-reperfusion injury - Li,Liang-da; Zhou,Yue; Shi,Shan-fen (PeerJ, 2024)
Background Cerebral ischemia (CI), ranking as the second leading global cause of death, is frequently treated by reestablishing blood flow and oxygenation. Paradoxically, this reperfusion can intensify tissue damage, leading to CI-reperfusion injury. This research sought to uncover biomarkers pertaining to protein processing in the endoplasmic reticulum (PER) during CI-reperfusion injury. Methods We utilized the Gene Expression Omnibus (GEO) dataset GSE163614 to discern differentially expressed genes (DEGs) and single out PER-related DEGs. The functions and pathways of these PER-related DEGs were identified via Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Core genes were pinpointed through protein-protein interaction (PPI) networks. Subsequent to this, genes with diagnostic relevance were distinguished using external validation datasets. A single-sample gene-set enrichment analysis (ssGSEA) was undertaken to pinpoint genes with strong associations to hypoxia and apoptosis, suggesting their potential roles as primary inducers of apoptosis in hypoxic conditions during ischemia-reperfusion injuries. Results Our study demonstrated that PER-related genes, specifically ADCY5, CAMK2A, PLCB1, NTRK2, and DLG4, were markedly down-regulated in models, exhibiting a robust association with hypoxia and apoptosis. Conclusion The data indicates that ADCY5, CAMK2A, PLCB1, NTRK2, and DLG4 could be pivotal genes responsible for triggering apoptosis in hypoxic environments during CI-reperfusion injury.
Keywords: Cerebral ischemia-reperfusion injury; Endoplasmic reticulum protein processing; Gene expression profiling; Protein-protein interactions; Hypoxia-inducible factor 1 alpha